Cement Industry Optimization, Characterization and Sustainable Application - El-Din Mostafa Saleh, Hosam (IntechOpen, 2021)
Cement is the basis of the building and construction industry and of fundamental importance for many civil engineering applications. As such, the cement industry is one of the key industries worldwide necessary for the current and future sustainable development of society. Despite its undisputed importance, the cement industry is one of those industrial branches predominately responsible for high energy consumption and excessive generation of large amounts of carbon dioxide and other contaminants that significantly endanger human health and the environment and contributes to global warming.In this context, nanomaterials, polymeric materials, and natural additives are being used for cement enhancement in various applications. This book examines these novel materials and their optimization, characterization, and sustainable application in the building industry and for stabilizing hazardous waste.